Lactose Engineering for Better Performance in Dry Powder Inhalers - Yahya Rahimpour; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2012)
Dry powder inhaler (DPI) is generally formulated as a powder mixture of coarse carrier particles and micronized drug with aerodynamic diameters of 1-5 μm. Carrier particles are used to improve drug particle flowability, thus improving dosing accuracy, minimizing the dose variability compared with drug alone and making them easier to handle during manufacturing operations. Lactose is the most common and frequently used carrier in DPIs formulations and nowadays various inhalation grades of lactose with different physico-chemical properties are available on the market. Therefore, the purpose of this manuscript is to review evolution of lactose as a carrier in inhalable formulations, their production and the impact of its physico-chemical properties on drug dispersion. This review offers a perspective on the current reported studies to modify lactose for better performance in DPIs.